Sclerostin - a potential new marker of exercise influence on vascular calcification and mineral and bone disorder in hemodialysed adults - Turon-Skrzypinska, Agnieszka; Dutkiewicz, Grazyna; Marchelek-Myśliwiec, Malgorzata; Ryl, Aleksandra; Uzdzicki, Artur; Przybylski, Tomasz; Rotter, Iwona (Journal of Education, Health and Sport, 2019)
Chronic Kidney Disease (CKD) is defined as abnormalities of kidney structure or function, present for >3 months, with implications for health. Amongst CKD complications the most fatal is cardiovascular disease, which together with Chronic Kidney Disease Mineral and Bone Disorder (CKD-MBD) share a possible origin in Wnt signaling pathway disturbances. Sclerostin, a potent Wnt signaling inhibitor may possibly be used as a potential new marker of exercise influence on vascular calcification and mineral and bone disorder in hemodialysed adults.